EFFECT OF SOCIAL SKILLS TRAINING (SST) TREATMENT WITH AND WITHOUT DIET CFGF ABILITY TO SOCIALIZATION AUTISM CHILDREN IN SLB AUTISM POTENTIAL CHILD DEVELOPMENT FOUNDATION (YPPA) PADANG 2018 - Ridhyalla Afnuhazi ((IJP) Indonesia Jurnal Perawat, 2018)
Number of persons with autism in the world range of 60.000 - 150.000 autism occurred in children aged below 15 years. Therapy was given to improvement of social skills in autistic children Social Skills Training Therapy (SST). The purpose of this study was to determine the ability of Socialization Effects of SST with and without diet CFGF for Autism Children in SLB Autism YPPA Padang 2018. Quasi - experimental design with one - group pre - post test. The population in this study all children with autism aged 6-12 year, and samples were taken by convenience sampling 20 people with and without diet CFGF. Univariate date processing techniques while the frequency distribution and central tedensy and Bivariate date processing techniques with paired T - test. Results of research abilities children with autism after therapy SST with and without diet CFGF with social skills of children with autism. Suggestions can be submitted to the study of nursing in order to detect early signs of the symptoms experienced by children with autism so there is no sign of severe symptoms and train the socialization skills of children with autism with SST therapy.